CLINICAL AND EPIDEMIOLOGICAL FEATURES OF TRUE ACANTHOLYTIC PEMPHIGUS IN AZERBAIJAN - Faragzheva, G.Z. (World of Medicine and Biology, 2024)
The purpose of the study was to assess the epidemiological condition and clinical course of true acantholytic pemphigus in Azerbaijan. 554 patients with true acantholytic pemphigus were involved in observation. We analyzed the dynamics in morbidity (coverage of a period from 1999 to 2011). It was found that there was a steady increase in the morbidity since 1999, and since 2006 the rate of disease growth has formed 6-year cycle. The course of the disease has changed, it has become more severe and resistant to the therapy. The number of patients with true acantholytic pemphigus increased in persons under 40 years of age (where there was a twofold predominance of women). The prevalence of common forms over limited, a reduction in the period of mucosal lesions, rejuvenation of the disease’s formation, resistance of the disease to the therapy (a twofold increase in the dose of glucocorticoids) make it possible to make judgments about the change in the course of the disease.